Uterine cervix cancer: Epidemiological and cytopathological analysis in the Municipality of São Luís, State of Maranhão, Brazil (Research, Society and Development, 2021)
Cervical cancer (CCU) is considered a serious public health problem, with a high incidence and high morbidity and mortality worldwide. This study aimed to evaluate the epidemiological and cytopathological profile of cervical cancer diagnosed in the city of São Luís in the period from 2015 to 2020. An epidemiological study of a descriptive nature and with a quantitative and retrospective approach was developed with data collected for the city of São Luís, Maranhão, Brazil. These data were collected from the Cancer Information System (SISCAN) and discussed based on articles published in journals and online database. A total of 302.532 exams performed during the study period were registered. The year 2019 had the highest number of exams (25,4%). The age group with the highest number of exams ranged from 30 to 39 years, totaling 25,5%. As for the suitability, 98,4% of the samples were classified as satisfactory. Squamous epithelium was the most represented in cytopathological samples (58%). Tracking (99,1%) the CCU was the main reason for taking the exam. Among benign cellular alterations, inflammation was the finding with the highest number of records (77,1%) and low-grade intraepithelial lesions were the most recurrent (1,12%) among cellular abnormalities. This study demonstrates the need for periodic preventive examinations for the diagnosis of CCU, since this type of cancer is preventable and curable, especially when lesions are diagnosed at an early stage.